Alcohol, crime and public health - Newbury-Birch, Dorothy (Routledge studies in crime and society, 2023)
"Alcohol, Crime and Public Health explores the issue of drinking in the criminal justice system, providing an overview of the topic from both a criminal justice and public health perspective. The majority of prisoners in the UK (70%) have an alcohol use disorder, and evidence tells us that risky drinking is high amongst those in contact with all areas of the criminal justice system. Uniquely, this book brings both a criminal justice and public health perspective to the topic. The book opens by exploring the levels of crime attributed to alcohol, the policy context of alcohol and crime, and the prevalence of risky alcohol consumption in the criminal justice system. The following chapters examine risky drinking amongst men, women and young people in the criminal justice system. The final chapters look at the efficacy of psychosocial interventions for risky drinking in the criminal justice system, and look forward to how researchers and practitioners can work together to produce research in the criminal justice system. Written in an accessible and concise style, Alcohol, Crime and Public Health will be of great use to students of Criminology, Criminal Justice, and Public Health as well as the wider area of Public and Social Policy in relation to alcohol and crime"--